Tres mirades sobre el cas Puig Antich - Fernàndez, Josep-Anton (Studia Romanica Posnaniensia, 2015)
The arrest, trial, and execution of the anarchist activist Salvador Puig Antich in 1974 were some of the most crucial events in the final years of general Franco’s regime. These facts gave rise to an enormous political mobilisation both in Catalonia and in Europe, and turned Puig Antich into a symbol of anti-Franco resistance within Catalan democratic culture. At the same time, due to both this symbolic status and the traumatic nature of the events, as well as the manifest injustice with which they concluded, the Puig Antich case has been the object of regular commemoration in the media and in diverse forms of cultural production. This makes it particularly interesting for an analysis of the uses of the past in Catalan culture. This article proposes a comparative analysis of three books on Puig Antich’s case that have been published in Catalan over a period of thirty years: La torna de la torna: Salvador Puig Antich i el M.I.L., by the Carlota Tolosa collective (1985), Compte enrere: La història de Salvador Puig Antich (2001), by Francesc Escribano, and Salvador Puig Antich, cas obert: La revisió definitiva del procés (2013), by Jordi Panyella. These three journalistic texts, published at different but highly significant historical moments, allow us to reflect on the rewriting of the Puig Antich case and its meaning for Catalan society, especially with regards to the political and national sentimentality they construct around the relationship of Catalan society with political violence and the trauma of Francoist repression.